Wspomnienia o zyciu kulturalnym i obyczajowym Lwowa : 1918-1939 - Tyrowicz, Marian (Wroclaw : Zaklad Narodowy im. Ossolinskich, 1991)
A memoire of life and customs in Lwow, 1918-1939, which was pre-World War II Poland.
Includes bibliographical references and index.
Keywords: Lʹviv (Ukraine) -- Civilization